WELLNESS TOURISM MOTIVATION OF GENERATION Z IN BALI: A STRUCTURAL EQUATION MODELING (SEM) APPROACH - Ismarizal, Beni; Islami, Fadillah Nur; Farhan, Aries (Faculty of Psychology Universitas Islam Sultan Agung Semarang, 2024)
Wellness tourism has gained increasing attention as individuals seek experiences that support physical, mental, and emotional well-being, especially among younger generations. Previous studies have highlighted that wellness tourism motivations often include stress relief, personal development, and the pursuit of unique experiences, yet research focusing specifically on Generation Z remains limited. This study validates the factors influencing wellness tourism motivation among Generation Z. Using a quantitative approach with a cross-sectional survey and purposive sampling of 310 respondents, motivational factors were analyzed through Structural Equation Modeling (SEM). The results show that Generation Z’s wellness tourism motivation is multidimensional, encompassing physical health, transcendence, escape from routine, care for others, new experiences, and self-esteem development. For this generation, wellness tourism functions not only as a form of recreation but also as a coping mechanism for modern life pressures, a medium for self-reflection, and a tool for personal growth and emotional recovery. These findings contribute theoretically by extending the literature on youth travel behavior and wellness motivation, while practically informing the design of tourism experiences that cater to Generation Z’s holistic well-being needs. Future research could investigate wellness tourism motivations across diverse cultural and regional contexts, adopt longitudinal designs to monitor motivational changes over time, and explore the influence of digital wellness platforms or social media on travel behavior. Additionally, qualitative studies could provide deeper insights into personal narratives and emotional experiences, enriching the understanding of how wellness tourism shapes the lifestyle and psychological well-being of young travelers.